Regression of Left Ventricular Mass after Implantation of the Sutureless 3f Enable Aortic Bioprosthesis - Concistrè, Giovanni (Tex Heart Inst J, 2015)
Left ventricular hypertrophy in aortic stenosis is considered a compensatory response for the maintenance of systolic function but a risk factor for cardiac morbidity and death. We investigated the degree of left ventricular mass regression after implantation of the sutureless Medtronic 3f Enable(®) Aortic Bioprosthesis. We studied 19 patients who, from May 2010 through July 2011, underwent isolated aortic valve replacement with the 3f Enable bioprosthetic valve, with clinical and echocardiographic follow-up at 6 months. The mean age was 77.1 ± 5.1 years (range, 68–86 yr); 14 patients were women (73.7%); and the mean logistic EuroSCORE was 15.4% ± 11.8%. Echocardiography was performed preoperatively, at discharge, and at 6 months' follow-up. The left ventricular mass was calculated by means of the Devereux formula and indexed to body surface area. The left ventricular mass index decreased from 146.1 ± 47.6 g/m(2) at baseline to 118.1 ± 39.8 g/m(2) at follow-up (P=0.003). The left ventricular ejection fraction did not change significantly. The mean transaortic gradient decreased from 57.3 ± 14.2 mmHg at baseline to 12.3 ± 4.6 mmHg at discharge and 12.2 ± 5.3 mmHg at follow-up (P <0.001), and these decreases were accompanied by substantial clinical improvement. No moderate or severe paravalvular leakage was present at discharge or at follow-up. In isolated aortic stenosis, aortic valve replacement with the 3f Enable bioprosthesis results in significant regression of left ventricular mass at 6 months' follow-up. However, this regression needs to be verified by long-term echocardiographic follow-up.